The Reflexive Pronoun of the Bidayuh-Somu Language: Its Comparable Process to English Language Suffix -self/-selves - Eusabinus Bunau (Lingua Cultura, 2021)
The research aimed to describe the reflexive pronoun of the language of the Bidayuh-Somu and English in terms of its formation process. The research data were reflexive pronoun of the Bidayuh-Somu language taken from the dissertation and the English language reflexive pronoun taken from the website. The method of research was comparative, and the technique of data analysis was descriptive. It is found that morphologically, the reflexive pronoun of the Bidayuh-Somu language is formed by attaching the prefix goni- that is derivational to free morpheme. In the English language, the reflexive pronoun is formed by affixing the suffix -self/-selves that is inflectional to free morpheme. The free morpheme, in the case of these two languages, is a personal pronoun. In terms of function, the two morphemes are both class-maintaining. Furthermore, in terms of word meaning, they are unchanged. The complex word the prefix goni- forms is prefixal, while the complex word the suffix -self/-selves forms are suffixal. The importance of comparing the prefix goni- with the suffix -self/-selves is to linguistically provide a description of similarities in terms of the morphological process for reflexive pronoun formation. Although the process of affixation is different, one employs derivational, and the other one applies inflectional. However, the description indicates that the two affixes are similar in terms of duty to reflexive pronoun formation. In the syntactic model of morphology, the use of the two reflexive pronouns is to intensify or emphasize the personal pronoun. They reflect upon the sentences’ subjects or as antecedents of the subjects in sentences.